Significance of Test-based Ratings for Metropolitan Boston Schools - Bolon, Craig (Education Policy Analysis Archives, 2001)
In 1998 Massachusetts began state-sponsored, annual achievement testing of all students in three public school grades. It has created a school and district rating system for which scores on these tests are the sole factor. It proposes to use tenth-grade test scores as a sole criterion for high school graduation, beginning with the class of 2003. The state is treating scores and ratings as though they were precise educational measures of high significance. A review of tenth-grade mathematics test scores from academic high schools in metropolitan Boston showed that statistically they are not. Community income is strongly correlated with test scores and accounted for more than 80 percent of the variance in average scores for a sample of Boston-area communities. Once community income was included in models, other factors–including percentages of students in disadvantaged populations, (Note 1) percentages receiving special education, percentages eligible for free or reduced price lunch, percentages with limited English proficiency, school sizes, school spending levels, and property values–all failed to associate substantial additional variance. Large uncertainties in residuals of school-averaged scores, after subtracting predictions based on community income, tend to make the scores ineffective for rating performance of schools. Large uncertainties in year-to-year score changes tend to make the score changes ineffective for measuring performance trends.